High-refractoriness-under-load anti-erosion mullite brick for cement kiln and preparation method thereof

By combining mercury stone, monoclinic zirconia, clay and silica fume in cement kiln mullite bricks, the problem of insufficient corrosion resistance of refractory bricks is solved, and high load softening temperature and excellent comprehensive performance are achieved. High-performance refractory materials suitable for cement kilns.

CN119430962APending Publication Date: 2025-02-14CHINA FIRST METALLURGICAL GROUP +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411805403.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing refractory bricks have insufficient corrosion resistance in cement kilns, and the thermal shock stability and corrosion resistance of mullite bricks prepared with high aluminum content are poor, making it difficult to coordinate high load and soft and corrosion resistance.

Method used

Using mullite homogenous material with high aluminum content as the main raw material, the anti-erosion, anti-permeability and thermal shock properties of mullite bricks are improved by compounding rosy, monoclinic zirconia, clay and silica fume, thereby achieving high Load softening temperature and excellent comprehensive performance.

Benefits of technology

The prepared high-load soft erosion-resistant mullite bricks show low porosity, high volume density, high pressure resistance at room temperature, strong thermal shock resistance, high load softening temperature, excellent corrosion resistance, and suitable for coordinated disposal of hazardous waste. The service life of the rotary kiln can be increased to more than 15 months.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179080250000041
    Figure BDA0005179080250000041
  • Figure BDA0005179080250000051
    Figure BDA0005179080250000051
  • Figure BDA0005179080250000052
    Figure BDA0005179080250000052
Patent Text Reader

Abstract

The invention belongs to the technical field of refractory materials, and discloses a high-refractoriness-under-load anti-erosion mullite brick for a cement kiln and a preparation method thereof. The mullite brick is prepared from the following raw materials in percentage by mass: 4 to 8 percent of mullite homogeneous material with the thickness of 5 to 3mm, 25 to 30 percent of mullite homogeneous material with the thickness of 3 to 1mm, 20 to 35 percent of mullite homogeneous material with the thickness of 1 to 0mm, 20 to 35 percent of andalusite with the thickness of 0.074 to 0.0374 mm, 1 to 5 percent of monoclinic zirconium oxide, 2 to 5 percent of clay, 1 to 2 percent of silica fume and a binding agent which is 2 to 6 percent of the total mass of the raw materials. The mullite homogeneous material with high aluminum content is taken as a main raw material, the mullite brick is endowed with high refractoriness under load, and the erosion resistance, permeation resistance and thermal shock resistance of the mullite brick are improved by compounding the andalusite, the monoclinic zirconia, the clay and the silica fume, so that the mullite brick has excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a high-load soft corrosion-resistant mullite brick for a cement kiln and a preparation method thereof. Background Art

[0002] The rotary kiln is the main equipment in the cement production process. The kiln lining is the refractory material inlaid on the inner surface of the rotary kiln cylinder. Its function is to protect the cylinder from high temperature and erosion damage. Increasing the safe operation cycle of the rotary kiln is one of the main measures for increasing production and saving in the cement industry. With the development of the coordinated disposal of cement kiln technology, the corrosion resistance of refractory bricks has been severely challenged. The increase in the circulation of alkali, chlorine and sulfur in the cement kiln has further aggravated the erosion of the kiln lining refractory materials; at the same time, the penetration of cement clinker in the refractory materials not only accelerates the damage of the refractory materials, but also seriously corrodes the cement rotary kiln cylinder, thus affecting its safe operation.

[0003] The utilization rate of bauxite resources in my country is low, a large amount of medium and low-grade ores are abandoned, and the waste of resources is serious. The application of homogeneous synthesis technology can effectively improve the utilization rate of medium and low-grade bauxite mineral resources, and has good energy-saving and environmental protection benefits. The mullite homogenous material prepared under this synthesis technology has the characteristics of perfect crystal phase development, stable volume, physical phase and performance at high temperature. The alumina content of commonly used mullite homogenous materials is 40% to 85%. Mullite bricks prepared from mullite homogenous materials with low alumina content (40%-60%) have excellent corrosion resistance, but the load softening temperature is relatively low, generally below 1550℃, while mullite bricks prepared with high aluminum content (70%-85%) have a higher load softening temperature, generally above 1600℃, but their thermal shock stability and corrosion resistance are poor. Therefore, coordinating high load softening and corrosion resistance is a difficult problem currently faced. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a high-load soft erosion-resistant mullite brick for cement kiln and a preparation method thereof in view of the deficiencies in the prior art. A mullite homogenous material with a high aluminum content is used as the main raw material to give the mullite brick a high load softening temperature, and by compounding andalusite, monoclinic zirconia, clay and silica fume, the erosion resistance, penetration resistance and thermal shock resistance are improved, thereby achieving excellent comprehensive performance.

[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a high-load soft erosion-resistant mullite brick for cement kiln, comprising the following raw materials in percentage by weight: 4-8% of 5-3mm mullite homogeneous material, 25-30% of 3-1mm mullite homogeneous material, 20-35% of 1-0mm mullite homogeneous material, 20-35% of 0.074-0.0374mm andalusite, 1-5% of monoclinic zirconia, 2-5% of clay, 1-2% of silica fume, and 2-6% of the total weight of the above raw materials as a binder.

[0006] In the above scheme, the Al of the mullite homogeneous material is 2 O 3 The content is 70-80wt%, Fe 2 O 3 Content ≤1.8wt%, TiO 2 Content ≤4wt%, K 2 O+Na 2 O content ≤ 0.6wt%.

[0007] In the above scheme, the bulk density of the mullite homogenous material is 2.75-3.10 g / cm 3 .

[0008] In the above scheme, the Al of the andalusite 2 O 3 The content is 50-60wt%, Fe 2 O 3 Content ≤1.5wt%, K 2 O+Na 2 O content ≤ 0.5wt%.

[0009] In the above scheme, the volume density of the andalusite is ≥3.2g / cm 3 .

[0010] In the above scheme, the monoclinic zirconium oxide ZrO 2 Content ≥98wt%.

[0011] In the above solution, the particle size of the monoclinic zirconium oxide is 0.074 to 0.0374 mm.

[0012] In the above scheme, the Al of the clay 2 O 3 Content ≥ 30wt%, Fe 2 O 3 Content ≤1.6wt%, K 2 O+Na 2 O content ≤ 0.5wt%.

[0013] In the above solution, the particle size of the clay is 0.074-0.0374 mm.

[0014] In the above scheme, the SiO 2 Content ≥92%, loss on ignition ≤2%.

[0015] In the above solution, the particle size of the silica fume is ≤10 μm.

[0016] In the above scheme, the binder is a dextrin aqueous solution or a calcium lignin sulfonate aqueous solution with a concentration of 1.1-1.2 g / cm 3 .

[0017] The present invention also provides a method for preparing high-load soft corrosion-resistant mullite bricks for cement kilns, comprising the steps of:

[0018] 1) dry-mixing homogeneous mullite materials of various particle sizes, adding a binder and mixing evenly, and then adding andalusite, monoclinic zirconia, clay and silica fume and mixing evenly to obtain a mixed material;

[0019] 2) The mixed material is pressed into shape, dried, then fired, and cooled to obtain high-load soft corrosion-resistant mullite bricks for co-processing cement kilns.

[0020] In the above scheme, the drying temperature is 100-150° C. and the drying time is 15-20 hours.

[0021] In the above scheme, the sintering temperature is 1350-1480°C, and the sintering temperature is kept for 3-4 hours.

[0022] In the above scheme, the heating system during the sintering process is: when the temperature is ≤1000°C, the heating rate is 9-10°C / min; when 1000°C<temperature<1350°C, the heating rate is 7-8°C / min; when the temperature is ≥1350°C, the heating rate is 5-6°C / min.

[0023] The design concept of the present invention is:

[0024] Based on the premise that the refractoriness temperature of mullite homogenous material with an aluminum content of 70-80% is high and the mullite bricks prepared therefrom have poor corrosion resistance and thermal shock resistance, andalusite, monoclinic zirconia and silica fume are compounded to prepare a corrosion-resistant mullite brick for a synergistically processed cement kiln.

[0025] On the one hand, the addition of silica fume can improve the formability of the products in the pressing process, increase the volume density of the products in the molding process, make the density of the semi-finished products higher, and ultimately improve the density of the products.

[0026] On the other hand, by optimizing the compounding ratio of mullite homogenous material to zirconium oxide and silica fume, a certain amount of glass phase can be precipitated inside the brick during high-temperature use, effectively filling the pores of the mullite brick, improving the density of the product, and improving the corrosion of potassium and sodium alkali vapor during use. At the same time, optimizing the compounding ratio of monoclinic zirconium oxide and silica fume will not affect the strength and load softening temperature of the mullite brick due to the precipitation of the liquid phase. In addition, the compounded monoclinic zirconium oxide can undergo phase change and produce microcracks at high temperatures, further improving the thermal shock resistance of the product.

[0027] Finally, during high-temperature service, 1-5% monoclinic zirconium oxide in mullite bricks reacts with calcium oxide in cement clinker to generate CaO·ZrO with high liquid viscosity. 2 , CaZrO 3 The generation, development and aggregation on the brick surface improves the kiln skin performance of mullite bricks. The kiln skin with uniform and stable thickness can effectively reduce the erosion of alkali, chlorine, sulfur and cement clinker, and improve the service life of the product.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The high-load soft erosion-resistant mullite brick prepared by the invention has an apparent porosity of 13-14% and a volume density of 2.65-2.75 g / cm 3 The room temperature compressive strength is 60-100MPa, the thermal shock stability (1100℃ water cooling) is ≥20 times, the load softening temperature is ≥1600℃, and the corrosion resistance is excellent.

[0030] The high-load soft erosion-resistant mullite bricks prepared by the present invention are particularly suitable for the coordinated disposal of hazardous waste rotary kilns. Compared with existing products such as silica-mullite bricks, they have excellent erosion resistance, penetration resistance and thermal shock resistance, and can increase their service life to more than 15 months, with significant economic and social benefits. DETAILED DESCRIPTION

[0031] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0032] In the following examples, the Al content of the mullite homogenous material used is 2 O 3 The content is 70-80%, Fe 2 O 3 Content ≤1.8%, TiO 2 Content ≤4%, K 2 O+Na 2 O content ≤ 0.6%, bulk density 2.75 ~ 3.10g / cm 3 ; Al in andalusite 2 O3 The content is 50-60%, Fe 2 O 3 Content ≤1.5%, K 2 O+Na 2 O content ≤ 0.5%, volume density ≥ 3.2g / cm 3 ; Monoclinic zirconium oxide ZrO 2 Content ≥98%, particle size 0.074~0.0374mm; Al in clay 2 O 3 Content ≥30%, Fe 2 O 3 Content ≤1.6%, K 2 O+Na 2 O content ≤ 0.5%, particle size 0.074 ~ 0.0374mm; SiO 2 Content ≥92%, ignition loss ≤2%, particle size ≤10μm; binder A concentration 1.2g / cm 3 dextrin aqueous solution, binder B has a concentration of 1.1 g / cm 3 Calcium lignin sulfonate aqueous solution, binder C concentration of 1.2g / cm 3 of calcium lignin sulfonate aqueous solution.

[0033] Example

[0034] In the following embodiments, the raw materials of high-load soft erosion-resistant mullite bricks for cement kilns include 5-3 mm mullite homogeneous material, 3-1 mm mullite homogeneous material, 1-0 mm mullite homogeneous material, 0.074-0.0374 mm andalusite, monoclinic zirconia, clay, and silica fume. The mass percentage of each raw material is shown in Table 1, and 2-6% of the total mass of the above raw materials is added as a binder. The selection and dosage of the binder are shown in Table 1.

[0035] Table 1

[0036]

[0037] In each embodiment, the method for preparing high-load soft erosion-resistant mullite bricks for cement kilns comprises the following steps:

[0038] 1) dry-mixing homogeneous mullite materials of various particle sizes for 1 to 2 minutes, then adding a binder and mixing evenly, and then adding andalusite, monoclinic zirconia, clay and silica fume and mixing for 3 to 5 minutes to obtain a mixed material;

[0039] 2) The mixed material is pressed into shape by a 630 or 1000 ton double screw press, dried, and then fired. The firing process adopts a three-stage heating system, the first stage is when the temperature is ≤1000°C, the second stage is when 1000°C < temperature <1350°C, and the third stage is when the temperature is ≥1350°C. Each stage adopts a different heating rate. After heating to the firing temperature, the temperature is kept constant and cooled to room temperature to obtain high-load soft corrosion-resistant mullite bricks for coordinated disposal cement kilns.

[0040] In each embodiment, the main parameters involved in the preparation process are shown in Table 2.

[0041] Table 2

[0042]

[0043] Comparative Example

[0044] The only difference between Comparative Example 1 and Example 1 is that no silica fume is added.

[0045] The only difference between Comparative Example 2 and Example 1 is that no silica fume is added.

[0046] The difference between Comparative Example 3 and Example 1 is that the Al 2 O 3 The content is 60%.

[0047] The performance of the high-load soft erosion-resistant mullite bricks for cement kilns in each embodiment and each comparative example was tested, and the results are shown in Table 3.

[0048] Table 3

[0049]

[0050]

[0051] Table 3 shows that the high-load soft erosion-resistant mullite brick prepared by the present invention has an apparent porosity of 13-14% and a bulk density of 2.65-2.75 g / cm 3 The room temperature compressive strength is 60-100MPa, the thermal shock stability (1100℃ water cooling) is ≥20 times, the load softening temperature is ≥1600℃, and it has excellent corrosion resistance, which is particularly suitable for the coordinated disposal of hazardous waste rotary kilns.

[0052] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A high-load soft erosion-resistant mullite brick for cement kiln, characterized in that: The invention comprises the following raw materials in percentage by weight: 4-8% of 5-3mm mullite homogeneous material, 25-30% of 3-1mm mullite homogeneous material, 20-35% of 1-0mm mullite homogeneous material, 20-35% of 0.074-0.0374mm andalusite, 1-5% of monoclinic zirconia, 2-5% of clay, 1-2% of silica fume, and 2-6% of the total weight of the above raw materials as a binder.

2. The high load soft corrosion resistant mullite brick for cement kiln according to claim 1, characterized in that: The Al2O3 content of the mullite homogeneous material is 70-80%, the Fe2O3 content is ≤1.8%, the TiO2 content is ≤4%, the K2O+Na2O content is ≤0.6%, and the bulk density is 2.75-3.10 g / cm 3 .

3. The high load soft corrosion resistant mullite brick for cement kiln according to claim 1, characterized in that: The andalusite has an Al2O3 content of 50-60%, a Fe2O3 content of ≤1.5%, a K2O+Na2O content of ≤0.5%, and a bulk density of ≥3.2 g / cm 3 .

4. The high load soft corrosion resistant mullite brick for cement kiln according to claim 1, characterized in that: The ZrO2 content of the monoclinic zirconium oxide is ≥98%, and the particle size is 0.074-0.0374 mm.

5. The high load soft corrosion resistant mullite brick for cement kiln according to claim 1, characterized in that: The clay has an Al2O3 content of ≥30%, a Fe2O3 content of ≤1.6%, a K2O+Na2O content of ≤0.5%, and a particle size of 0.074-0.0374 mm.

6. The high load soft corrosion resistant mullite brick for cement kiln according to claim 1, characterized in that: The SiO2 content of the silica fume is ≥92%, the ignition loss is ≤2%, and the particle size is ≤10μm.

7. The high load soft corrosion resistant mullite brick for cement kiln according to claim 1, characterized in that: The binder is a dextrin aqueous solution or a calcium lignin sulfonate aqueous solution with a concentration of 1.1 to 1.2 g / cm 3 .

8. The high load soft corrosion resistant mullite brick for cement kiln according to claim 1, characterized in that: The high-load soft erosion-resistant mullite brick for cement kiln has an apparent porosity of 13-14% and a bulk density of 2.65-2.75 g / cm 3 The compressive strength at room temperature is 60-100MPa, the thermal shock stability at 1100℃ water cooling is ≥20 times, and the load softening temperature is ≥1600℃.

9. A method for preparing high-load soft corrosion-resistant mullite bricks for cement kiln according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) dry-mixing homogeneous mullite materials of various particle sizes, adding a binder and mixing evenly, and then adding andalusite, monoclinic zirconia, clay and silica fume and mixing evenly to obtain a mixed material; 2) After the mixed material is pressed into shape, it is dried and then fired at a temperature of 1350-1480° C. The mixture is kept at the firing temperature for 3-4 hours and cooled to obtain a high-load soft corrosion-resistant mullite brick for a synergistic cement kiln.

10. The method for preparing high-load soft corrosion-resistant mullite bricks for cement kiln according to claim 9, characterized in that: The heating system during the sintering process is: when the temperature is ≤1000°C, the heating rate is 9-10°C / min; when 1000°C<temperature<1350°C, the heating rate is 7-8°C / min; when the temperature is ≥1350°C, the heating rate is 5-6°C / min.

Citation Information

Patent Citations

  • Large-scale, specially shaped mullite-corundum system sintered refractory material product and preparing technique thereof

    CN101367666A

  • Zirconium-containing re-sintered electrically-fused mullite brick and preparation method thereof

    CN109336575A

  • Molten iron tank bottom impact area precast block and preparation method thereof

    CN117700244A

  • High-strength mullite self-flowing castable and preparation method thereof

    CN117756512A